A Main Class of Integral Inequalities with Applications. Issue 4 (3rd July 2016) - Masjed-Jamei, Mohammad; Omey, Edward; Dragomir, Sever S.
Abstract: In this paper, we define some integral transforms and obtain suitable bounds for them in order to introduce a main class of integral inequalities including Ostrowski and Ostrowski-Grüss inequalities and various kinds of new integral inequalities. In this sense, we also introduce a three point quadrature formula and obtain its error bounds.